Curriculum Management In Strengthening The Quality Of Graduates Of Pesantren-Based Islamic Senior High Schools - Agus Ali; Dian Dian (Lafadz Jaya Publisher, 2024)
The objective of this research is to describe how curriculum planning, organization, implementation, and supervision strengthen the quality of graduates from pesantren-based Islamic senior high schools. The conceptual framework of this study posits that if educational institutions, including pesantren-based madrasahs, can continuously apply planning, organization, implementation, and supervision according to customer needs, then pesantren-based Islamic senior high schools can produce quality graduates. The research method used in this study is descriptive with a qualitative approach. Data collection techniques include documentary study, interviews, and observations.The research findings indicate that: 1) Curriculum planning in enhancing the quality of graduates from pesantren-based madrasahs at Ummul Quro Al-Islami Leuwiliang Bogor Islamic Senior High School and Sahid Pamijahan Bogor Islamic Senior High School includes goal setting, method determination, content determination, and evaluation determination. 2) Curriculum organization in enhancing the quality of graduates from pesantren-based madrasahs at Ummul Quro Al-Islami Leuwiliang Bogor Islamic Senior High School and Sahid Pamijahan Bogor Islamic Senior High School involves the preparation of academic calendars, scheduling of lessons, arrangement of duties and obligations of educational personnel, and school activity programs. 3) Curriculum implementation in enhancing the quality of graduates from pesantren-based madrasahs at Ummul Quro Al-Islami Leuwiliang Bogor Islamic Senior High School and Sahid Pamijahan Bogor Islamic Senior High School includes learning materials, learning strategies and methods, learning facilities and infrastructure, and learning assessment systems. 4) Curriculum supervision in enhancing the quality of graduates from pesantren-based madrasahs at Ummul Quro Al-Islami Leuwiliang Bogor Islamic Senior High School and Sahid Pamijahan Bogor Islamic Senior High School comprises evaluation of educational goals, evaluation of content or materials, evaluation of teaching strategies, and evaluation of assessment programs. 5) The quality of graduates resulting from curriculum management at Ummul Quro Al-Islami and Sahid Islamic Senior High Schools is good; both schools have graduates who are accepted by educational customers, especially universities, both public and private.